1980
DOI: 10.1159/000158233
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Investigation of Sudanophilic Lesions around the Aortic Ostia of Human Fetuses, Newborn and Children

Abstract: The sudanophilic lesions around the aortic ostia of 10 fetuses, 10 newborns and 10 children aged up to 1 year were studied using a polar coordinate mapping method. The periorificial sudanophilic lesions develop initially distal to the orifices and show a continuous increase with age in percentage and extent. In children the lesions nearly completely surround all the ostia with a significant distal peak. There was no sex difference; the involvement of the right and left side was comparable. The comparison of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 11 publications
(13 reference statements)
2
28
0
Order By: Relevance
“…The nonuniform distribution of lesions was thought to be a useful way of establishing mechanisms and a test of the relevance of the model to human disease; attention was drawn to the similar pattern occurring in young children. Parallels between the distributions in hyperlipidemic rabbits 10 -16 and children 1 were later confirmed by quantitative mapping techniques. However, it also emerged that disease has a different distribution in adult human arteries.…”
Section: Discussionmentioning
confidence: 74%
“…The nonuniform distribution of lesions was thought to be a useful way of establishing mechanisms and a test of the relevance of the model to human disease; attention was drawn to the similar pattern occurring in young children. Parallels between the distributions in hyperlipidemic rabbits 10 -16 and children 1 were later confirmed by quantitative mapping techniques. However, it also emerged that disease has a different distribution in adult human arteries.…”
Section: Discussionmentioning
confidence: 74%
“…In human foetuses, neonates and infants, fatty streaks occur around the downstream margins of these branch ostia (Sinzinger et al 1980). At later ages, however, they occur at the lateral and then the upstream margins (Sloop et al 1998), while advanced disease tends to completely surround the ostium (Mitchell & Schwartz 1965).…”
Section: Introductionmentioning
confidence: 99%
“…12 ' 3 Much effort has focused on the effects of hemodynamic shear stress on endothelial cells, since these cells are thought to play a pivotal role in atherogenesis. 4 In vivo studies have shown that the shape and orientation of endothelial cells is determined primarily by the blood flow.…”
mentioning
confidence: 99%